RANCANG BANGUN MODEL CUSTOMER RELATIONSHIP MANAGEMENT (CRM) PADA PERPUSTAKAAN SMP NEGERI 219 JAKARTA - Tri Setyo Slamet; Indah Sataria (Nindikayla Institute, 2025)
The school library plays a strategic role as a learning resource center that supports the educational process, strengthens literacy, and improves the quality of learning for students and teachers. However, library services at SMP Negeri 219 Jakarta are still managed manually, from searching the book collection, borrowing, and returning books, to compiling transaction reports, resulting in various challenges such as slow service, low work efficiency, and difficulties for users in accessing collection information. This study aims to design a web-based library system as a form of transformation for school library services through a user-satisfaction-oriented approach. The research employs a system design method using the Unified Modeling Language (UML) approach for system analysis and design, while system implementation utilizes the PHP programming language and the MySQL database. The developed system is equipped with features for book search, digital borrowing, book reservations, book donations, feedback and suggestions, return notifications, and automated reports. The research results indicate that the designed system is capable of improving the effectiveness of library management, accelerating service access, and enhancing user comfort and satisfaction. Thus, the digital transformation of school libraries serves as a strategic solution for improving the quality of library services based on user needs.